Anchorage-Independent Transcription of the Cyclin A Gene Induced by the E7 Oncoprotein of Human Papillomavirus Type 16 - Schulze, Almut (American Society for Microbiology, 1998)
To develop an experimental model for E7-mediated anchorage-independent growth, we studied the ability of E7-expressing NIH 3T3 subclones to enter S phase when they were cultured in suspension. We found that expression of E7 prevents the inhibition of cyclin E-associated kinase and also triggers activation of cyclin A gene expression in suspension cells. A point mutation in the amino terminus of E7 prevented E7-driven rescue of cyclin E-associated kinase activity in suspension cells; however, cells with this mutation retained some ability to activate cyclin A gene expression and promote S-phase entry. Activation of cyclin A gene expression by E7 was correlated with an increased binding of free E2F to a regulatory element in the cyclin A promoter which mediates both repression of cyclin A upon loss of adhesion and its reactivation by E7. Surprisingly, expression of E7 led to a nuclear accumulation of one species of free E2F, namely, an E2F-4–DP-1 heterodimer, that is exclusively cytoplasmic in the absence of E7. Taken together, the data reported here indicate that several different E7-dependent changes of cellular-growth-regulating pathways can cooperate to allow adhesion-independent entry into S phase.